2021
DOI: 10.1093/aler/ahab005
|View full text |Cite
|
Sign up to set email alerts
|

Litigation Spending and Care under the English and American Rules: Experimental Evidence

Abstract: We investigate the effects of fee-shifting in an experimental litigation game. In our setup, a defendant may cause harm to a plaintiff. The defendant can take precautions to lower the probability of harm at a personal cost. In case of harm, the parties go to court, where the winner is determined by a rent-seeking contest. We compare two fee-shifting rules: under the American rule each party bears its own litigation costs; under the English rule the loser has to reimburse the winner’s expenses. We test the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The findings are mixed. For instance, while Coursey and Stanley (1988) and Coughlan and Plott (1998) both found that settlement rates were significantly higher under the English Rule than under the American Rule, Massenot et al (2016) observed no significant differences. Importantly, Massenot et al (2016) revealed that each rule had its own costs and benefits (e.g.…”
Section: Do Legal Rules Affect Individuals' Litigation Behaviour?mentioning
confidence: 95%
See 3 more Smart Citations
“…The findings are mixed. For instance, while Coursey and Stanley (1988) and Coughlan and Plott (1998) both found that settlement rates were significantly higher under the English Rule than under the American Rule, Massenot et al (2016) observed no significant differences. Importantly, Massenot et al (2016) revealed that each rule had its own costs and benefits (e.g.…”
Section: Do Legal Rules Affect Individuals' Litigation Behaviour?mentioning
confidence: 95%
“…For instance, while Coursey and Stanley (1988) and Coughlan and Plott (1998) both found that settlement rates were significantly higher under the English Rule than under the American Rule, Massenot et al (2016) observed no significant differences. Importantly, Massenot et al (2016) revealed that each rule had its own costs and benefits (e.g. the American Rule was more efficient at the trial stage, whereas the English Rule performed better in incentivising ex-ante precautionary behaviours).…”
Section: Do Legal Rules Affect Individuals' Litigation Behaviour?mentioning
confidence: 95%
See 2 more Smart Citations
“…Experimental evidence supporting that emotions such as anger are very relevant for understanding retaliatory behavior such as punishment abounds (e.g., Bolle et al 2014, Bosman and van Winden 2002, Galeotti 2015, Reuben and van Winden 2008, Xiao and Houser 2005, van Winden 2007. Our paper is also related to a small line of literature using experimental economics to study decision-making in litigation, which has examined the impacts of whether the judicial system is adversarial or inquisitorial (Block and Parker 2004), of litigants delegating decisions to attorneys (Croson and Mnookin 1997) and how this delegation is governed contractually (McKee et al 2007) While Coughlan and Plott (1997) and Massenot et al (2017) also analyze experimentally decision-making in a litigation contest, neither of them considers the impact of emotions thereon.…”
Section: Introductionmentioning
confidence: 99%